Practice patterns for chronic hypoparathyroidism: data from patients and physicians in France. Issue 1 (31st January 2022) - Bertocchio, Jean-Philippe; Grosset, Natalie; Groussin, Lionel; Kamenický, Peter; Larceneux, Fabrice; Lienhardt-Roussie, Anne; Linglart, Agnès; Maruani, Gérard; Mirallie, Eric; Pattou, François; Seervai, Riyad N H; Sido, Coralie; et al.
Abstract : Context: Recent guidelines have provided recommendations for the care of patients with chronic hypoparathyroidism. Very little is known about actual physicians' practices or their adherence to such guidelines. Objective: To describe the physicians' practice patterns and their compliance with international guidelines. Design: The cohort studies included were Épi-Hypo (118 physicians and 107 patients, from September 2016 to December 2019) and ePatients (110 patients, November 2019). Methods: Internet-based cohorts involving all settings at a nationwide level (France). Participants were (i) physicians treating patients with chronic hypoparathyroidism and patients with chronic hypoparathyroidism either participating in the (ii) Épi-Hypo study (Épi-Hypo 2019 patients), or (iii) Hypoparathyroidism France, the national representative association (ePatients). Results: The physicians' specialties were mainly endocrinology (61%), nephrology (28%), family medicine (2.5%), pediatrics (2.5%), rheumatology (2%), or miscellaneous (4%) and 45% were practicing in public universities. The median number of pharmaceutical drug classes prescribed was three per patient. The combination of active vitamin D and calcium salt was given to 59 and 58% of ePatients and Épi-Hypo 2019 patients, respectively. Eighty-five percent of ePatients and 87% of physicians reported monitoring plasma calcium concentrations at a steady state at least twice a year. In 32 and 26% of cases, respectively, ePatients and physicians reported being fully in accordance with international guidelines that recommend targeting symptoms, plasma calcium and phosphate values, and urine calcium excretion. Conclusions: The care of patients with chronic hypoparathyroidism involves physicians with very different practices, so guidelines should include and target other specialists as well as endocrinologists. Full adherence to the guidelines is low in France.